Procedural and evidentiary aspects of medical and healthcare liability. The handling of sensitive data in Colombia - López-Oliva, José; Alarcón-Peña, Andrea; Luna-Salas, Fernando (Journal of Posthumanism, 2024)
This research work aims to analyze the violation of the patient’s rights to freedom and privacy and, in general, to habeas data incorporated in the so-called digital evidence. It seeks to demonstrate that, when weighing the rights to privacy and information of the medical user, the protection of habeas data prevails. The prevalence is established through the constitutional actions of group, popular, compliance and tutelage, which seek the prevention and in turn the sanction, for the violation of the human rights of the user of the health service. The research has a qualitative approach, with an exploratory scope. The research method used was the critical hermeneutic method promoted by Hans George Gadamer, and the techniques of conversation with experts and the relevant documentary search.